Medical Imaging Systems: A Physics-Based Approach to Improving Diagnostics and Patient Care - Mahmood, Yamama Hameed; Rahma, Tabark Shaker; Adan, Teabaa Adil; Jabbar, Mohammed Abdul Mohsen; Kadhim, Basheer Jawad (American Journal of Botany and Bioengineering, 2025)
Medical imaging plays a pivotal role in modern diagnostics and patient management, yet limitations in image resolution, modality integration, and interpretation persist, especially in complex clinical environments. Despite rapid technological advancements, a clear gap remains in integrating physics-based methodologies and emerging imaging technologies to optimize diagnostic accuracy. This study applies a multidisciplinary approach combining fundamental physics principles, quantum mechanics, signal detection theory, and data-driven modeling to examine existing and emerging imaging modalities including MRI, CT, PET, ultrasound, and hybrid systems. The research emphasizes the role of image acquisition techniques, reconstruction algorithms, noise reduction, and 3D imaging in enhancing diagnostic efficiency. The implications point toward a transformative potential of integrating physics-informed imaging systems with AI and quantum technologies to improve precision medicine, reduce diagnostic errors, and expand accessibility in diverse clinical settings.